2014
DOI: 10.1186/1471-2458-14-583
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with hardcore smoking in Poland: Findings from the Global Adult Tobacco Survey (2009–2010)

Abstract: BackgroundEstimating the prevalence of hardcore smoking and identifying linked factors is fundamental to improve planning and implementation of effective tobacco control measures. Given the paucity of data on that topic, we aimed to assess the prevalence of and factors associated with hardcore smoking in Poland.MethodsWe used data from the Global Adult Tobacco Survey (GATS). GATS is a representative, cross-sectional, household based survey conducted in Poland between 2009 and 2010. Binary logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
2
19
0
1
Order By: Relevance
“…The summative score was then divided into, high, medium low. Analogous methodology has been implemented elsewhere [19]. Additionally, awareness of the negative health consequences of smoking was assessed.…”
Section: Study Variablesmentioning
confidence: 99%
“…The summative score was then divided into, high, medium low. Analogous methodology has been implemented elsewhere [19]. Additionally, awareness of the negative health consequences of smoking was assessed.…”
Section: Study Variablesmentioning
confidence: 99%
“…Although there were controversies in the definitions of hardcore smoking, 10 several studies attempted to quantify the extent of hardcore smoking and to characterize hardcore smokers. [11][12][13][14][15][16][17][18] While hardcore smokers are usually characterized as regular smokers with heavy nicotine dependence, a lack of recent quit attempts and no intention to quit, some studies also included an additional criterion: they were 25 years and older. Among studies with the additional age criterion and used samples of smokers aged over 25, recent estimates indicated that 13.7% were considered hardcore in US and 14.3% in Canada and ranged from 23% in Norway to 39.9% in Poland in European countries.…”
Section: -9mentioning
confidence: 99%
“…This hypothesis states that with the declining prevalence and growing social disapproval of smoking, smokers become increasingly socially disadvantaged [4, 5]. Hardcore smoking has become a major public health challenge for tobacco control and cancer prevention [1, 68]. So-called « Hard-core Smokers » (HCS) seem to be unaffected by prevention campaigns and tax increases on tobacco products: most of them have no intention, and never have had, to stop smoking because they love smoking and do not believe in its dangers [9–12].…”
Section: Introductionmentioning
confidence: 99%